Electromagnetic Energy Redistribution in Coupled Chiral Particle Chain-Film System - Yuxia Tang; Yingzhou Huang; Linhong Qv; Yurui Fang (Nanoscale Research Letters, 2018)
Abstract Metal nanoparticle-film system has been proved that it has the ability of focusing light in the gap between particle and film, which is useful for surface-enhanced Raman scattering and plasmon catalysis. The rapid developed plasmonic chirality can also be realized in such system. Here, we investigated an electromagnetic energy focusing effect and chiral near-field enhancement in a coupled chiral particle chain on gold film. It shows large electric field enhancement in the gap between particle and film, as well as chiral near field. The enhancement properties at resonant peaks for the system excited by left circularly polarized light and right circularly polarized light are obviously different. This difference resulted from the interaction of circularly polarized light and the chiral particle-film system is analyzed with plasmon hybridization. The enhanced optical activity can provide promising applications for the enhancement of chiral molecule sensor for this chiral particle chain-film system.